Intermetallics in CP-Ti/X65 bimetallic sheets filled with Cu-based flux-cored wires. (15th January 2016) - Chu, Qiaoling; Zhang, Min; Li, Jihong; Fan, Qingyang; Xie, Weiwei; Bi, Zongyue
Abstract: This work is aimed to join the explosion-bonded CP-Ti/X65 bimetallic sheets with Cu-based flux-cored wires. Tungsten-inert gas (TIG) welding method was applied. The effect of V ratio on microstructure and mechanical properties was investigated. Ti–Fe, Ti–Cu and Ti–Cu–Fe intermetallics were identified in the reaction zones. The results showed that enhancing V ratio in the flux-cored wires led to the extension of the reaction zones, which eventually decreased the crack susceptibility of the joints. With V ratio rising to 25 wt.%, a sound joint was obtained. The ultimate strength of the joints fit the requirements. However, the bend tests showed extremely low bend ductility. Enhancing V ratio in the filler metals allowed diluting but not suppressing the formation of brittle intermetallics. Graphical abstract: Highlights: Cu15V, Cu20V and Cu25V were designed to join CP-Ti/X65 bimetallic sheets. The joint free from cracks was obtained with Cu25V flux-cored wire. The reaction zones became wider with increasing V ratio. V acted as bridge in bonding Cu and Ti.